Expression patterns and prognostic relevance of subtype-specific transcription factors in surgically resected small-cell lung cancer: an international multicenter study - Megyesfalvi, Zsolt; Barany, Nandor; Lantos, Andras; Valko, Zsuzsanna; Pipek, Orsolya; Lang, Christian; Schwendenwein, Anna; Oberndorfer, Felicitas; Paku, Sandor; Ferencz, Bence; Dezso, Katalin; Fillinger, Janos; et al. (The Journal of pathology, 2022)
The tissue distribution and prognostic relevance of subtype-specific proteins (ASCL1, NEUROD1, POU2F3, YAP1) present an evolving area of research in small-cell lung cancer (SCLC). The expression of subtype-specific transcription factors and P53 and RB1 proteins were measured by immunohistochemistry (IHC) in 386 surgically resected SCLC samples. Correlations between subtype-specific proteins and in vitro efficacy of various therapeutic agents were investigated by proteomics and cell viability assays in 26 human SCLC cell lines. Besides SCLC-A (ASCL1-dominant), SCLC-AN (combined ASCL1/NEUROD1), SCLC-N (NEUROD1-dominant), and SCLC-P (POU2F3-dominant), IHC and cluster analyses identified a quadruple-negative SCLC subtype (SCLC-QN). No unique YAP1-subtype was found. The highest overall survival rates were associated with non-neuroendocrine subtypes (SCLC-P and SCLC-QN) and the lowest with neuroendocrine subtypes (SCLC-A, SCLC-N, SCLC-AN). In univariate analyses, high ASCL1 expression was associated with poor prognosis and high POU2F3 expression with good prognosis. Notably, high ASCL1 expression influenced survival outcomes independently of other variables in a multivariate model. High POU2F3 and YAP1 protein abundances correlated with sensitivity and resistance to standard-of-care chemotherapeutics, respectively. Specific correlation patterns were also found between the efficacy of targeted agents and subtype-specific protein abundances. In conclusion, we investigated the clinicopathological relevance of SCLC molecular subtypes in a large cohort of surgically resected specimens. Differential IHC expression of ASCL1, NEUROD1, and POU2F3 defines SCLC subtypes. No YAP1-subtype can be distinguished by IHC. High POU2F3 expression is associated with improved survival in a univariate analysis, whereas elevated ASCL1 expression is an independent negative prognosticator. Proteomic and cell viability assays of human SCLC cell lines revealed distinct vulnerability profiles defined by transcription regulators. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
Keywords: molecular subtypes; regulace genové exprese u nádorů; Proteomics; Small Cell Lung Carcinoma; proteomika; expression pattern; ASCL1; immunohistochemistry; Humans; transkripční faktory bHLH; Transcription Factors; prognóza; small cell lung cancer; Prognosis; NEUROD1; prognostic relevance; YAP1; malobuněčný karcinom plic; Lung Neoplasms; Cell Line, Tumor; nádorové buněčné linie; Gene Expression Regulation, Neoplastic; transkripční faktory; Basic Helix-Loop-Helix Transcription Factors; POU2F3; lidé; nádory plic; neuroendocrine subtypes